If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5 + -1x = -2x + -3 Reorder the terms: -5 + -1x = -3 + -2x Solving -5 + -1x = -3 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -5 + -1x + 2x = -3 + -2x + 2x Combine like terms: -1x + 2x = 1x -5 + 1x = -3 + -2x + 2x Combine like terms: -2x + 2x = 0 -5 + 1x = -3 + 0 -5 + 1x = -3 Add '5' to each side of the equation. -5 + 5 + 1x = -3 + 5 Combine like terms: -5 + 5 = 0 0 + 1x = -3 + 5 1x = -3 + 5 Combine like terms: -3 + 5 = 2 1x = 2 Divide each side by '1'. x = 2 Simplifying x = 2
| 24x-5-13x+3=26x-3-15+1 | | 6x+9-5x=-2 | | Y-3x=1.7 | | 9x^2+x-1=0 | | x+.0507x=1630 | | 8x-(6x+7)=-1 | | 4+4x=3x+9 | | -5(t-3)+8t=6t-5 | | 6.4x=2.56 | | 8x-(6x+4)=10 | | 12x^2-10+37x=0 | | 16x^2-7x-9=0 | | 6-10*x=26-17*x | | (2s+1)(12s^2-17s+6)=0 | | y^2+2y-6=-y+4 | | 9(10+x)=108 | | 8(9x-5)=-2x | | z+17=19 | | 6x=7-4x | | -17+7*x=9*x+15 | | 8d-2d+2d+6=3d | | -18-5x=9x+23 | | 3x-5+2x=-50 | | 6x-2=4x-8 | | 5+7=106-6x | | 146-3*x=6*x+20 | | 3n=n+5 | | -10-5*x=8-8*x | | -5-20=2n-6 | | 3.4=20(x) | | 48-3+3c=45 | | 10n+1=5n+9 |